Multinational cooperation on challenging energy technologies: 'ITER Project' an EU mission. - Kiani, Aliakbar (Innovation: The European Journal of Social Sciences, 2025)
In recent decades, the trend of globalization has intensified as a result of the development of technologies and has brought nations closer together. Thus, the closer the minds of the people of the world become, the more similar their needs and demands become. National governments have to meet these needs as universal public goods. Naturally, resources are not consistently distributed around the world, and scientific achievements are limited to a few centers. Therefore, governments have to turn to transnational cooperation to fulfill their governance commitments. Institutionalists interpret international cooperation in the age of globalization as inevitable and in service of the public good. In this article, the development of technology on the process of globalization and multinational cooperation in a very sensitive field such as nuclear energy realized in the framework of the ITER project is discussed, which is a model for global-Local governance promotes by EU.